The public perception of nurses. An Italian cross-sectional study - Rubbi, Ivan; Cremonini, Valeria; Artioli, Giovanna; Lenzini, Annalisa; Talenti, Irene; Caponnetto, Valeria; La Cerra, Carmen; Petrucci, Cristina; Lancia, Loreto (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: The public opinion about the nursing profession can influence health service users, the work performance of nurses, health policies, and the choice to become a nurse. The aim of this study was to investigate the perception of nursing in modern society. Methods: A cross-sectional study was conducted with a sample of 398 participants belonging to four population groups: Very Important Persons (VIPs), general population, upper-school students, and nursing students. This phenomenon was assessed through the Nursing Attitude Questionnaire (NAQ) and several additional items. Results: The results highlighted that general population and nursing students showed a significantly better image of nurses than did VIPs and upper-school students. Conclusions: Overall, the sample acknowledged nurses fundamental connotations and functions, although secondary school students poorly recognized nurses’ professional autonomy, and VIPs’ judgements seemed to be more sensitive to the image of nurses given by mass media.